2015
DOI: 10.1111/jsr.12306
|View full text |Cite
|
Sign up to set email alerts
|

Napping facilitates word learning in early lexical development

Abstract: SUMMARYLittle is known about the role that night-time sleep and daytime naps play in early cognitive development. Our aim was to investigate how napping affects word learning in 16-month-olds. Thirty-four typically developing infants were assigned randomly to nap and wake groups. After teaching two novel object-word pairs to infants, we tested their initial performance with an intermodal preferential looking task in which infants are expected to increase their target looking time compared to a distracter after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 35 publications
1
79
0
Order By: Relevance
“…In addition, a further experiment by the above researchers on a similar group of 15-month-old infants showed that the nap-dependent benefits towards language learning (where infants learnt abstract grammatical relations) persisted even after 24 hours 27. A recent study by a separate group of researchers also highlighted nap-dependent benefits towards language in terms of vocabulary learning 28. In the study, Horváth et al found that 16-month-old infants who napped after learning sets of new object–word associations spent more time looking at the correct associative pairing at the 2-hour delayed test session, whereas infants who remained awake did not display any differences in looking between the learning and delayed test sessions.…”
Section: Resultsmentioning
confidence: 86%
“…In addition, a further experiment by the above researchers on a similar group of 15-month-old infants showed that the nap-dependent benefits towards language learning (where infants learnt abstract grammatical relations) persisted even after 24 hours 27. A recent study by a separate group of researchers also highlighted nap-dependent benefits towards language in terms of vocabulary learning 28. In the study, Horváth et al found that 16-month-old infants who napped after learning sets of new object–word associations spent more time looking at the correct associative pairing at the 2-hour delayed test session, whereas infants who remained awake did not display any differences in looking between the learning and delayed test sessions.…”
Section: Resultsmentioning
confidence: 86%
“…Friedrich et al, 2015;Gómez et al, 2006;Horváth et al, 2015;Hupbach et al, 2009). Seehagen, Konrad, Herbert, andSchneider (2015), who tested memory in 6-month-olds, did not observe reduced retention across testing after a nap, but their test did not involve presenting inconsistent information from encoding.…”
Section: Behavioral Resultsmentioning
confidence: 92%
“…Friedrich and Friederici (2011) reported an N400 event-related potential, indicative of semantic memory, for newly encoded word forms at 6 months that diminished significantly the next day. However, sleep soon after encoding aids new language retention in infants age 9 months and older (Friedrich, Wilhelm, Born, & Friederici, 2015;Gómez, Bootzin, & Nadel, 2006;Horváth, Myers, Foster, & Plunkett, 2015;Hupbach, Gómez, Bootzin, & Nadel, 2009). This led us to ask whether sleep will affect retention of new word learning at an earlier age.…”
Section: Introductionmentioning
confidence: 98%
“…In another study, Horvath et al studied word learning in 34 infants of 16 months using object-word associations 147 . After a 2-hour delay, memory performance increased for the nap group but not for the wake group.…”
Section: Napping and Memory Functions In Childrenmentioning
confidence: 99%